2015
DOI: 10.1563/aaid-joi-d-12-00178
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival Rates of Implants Supporting Overdentures

Abstract: The study aims were to evaluate survival rates of dental implants in patients wearing maxillary and mandibular overdentures in relation to age, sex, smoking, implant splinting or non-splinting, the maxilla rehabilitated, and number of implants per dental arch. This was a prospective study of patients who were completely edentulous in either mandible or maxilla or both, rehabilitated with implant-retained overdentures, with a follow-up of at least 3 years. 95 patients with 107 overdentures were supported by 360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
4
37
0
1
Order By: Relevance
“…The oral rehabilitation of edentulous jaw by combining 4 implants, 2 straight medially and 2 tilted distally, was developed to overcome the anatomic limitations related to bone loss, and where it is difficult to treat the patients without complex augmentative techniques [3, 4]…”
Section: Introductionmentioning
confidence: 99%
“…The oral rehabilitation of edentulous jaw by combining 4 implants, 2 straight medially and 2 tilted distally, was developed to overcome the anatomic limitations related to bone loss, and where it is difficult to treat the patients without complex augmentative techniques [3, 4]…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the great majority of the studies showed different numbers of implants for the rehabilitation of maxillary edentulous patients. It has been reported in long terms of results that the installation of six implants in the maxilla would be the best strategy to obtain good dental implants survival rates [30,34]. Therefore, the use of six implants for maxillary IODs was expected to present satisfactory results by performing a favorable distribution of the masticatory loads under the prosthesis, but with a higher cost and, eventually, with a bone grafting requirement.…”
Section: Discussionmentioning
confidence: 99%
“…The resorptive pattern of the maxilla, when extensive, may also lead to dissatisfaction with certain prosthetic designs, since almost 90% have a smile extended to second premolars, which impacts buccal corridor esthetics . Given these risk factors, it is not surprising that the survival rate and patient satisfaction of maxillary implant prostheses is lower than similar data reported on the mandible . Because of these challenges, there continues to be controversy on the appropriate implant treatment for the edentulous maxilla.…”
Section: Sackett's Hierarchy Of Evidencementioning
confidence: 99%
“…Three assessments are critical to a proper selection of prosthetic design: esthetic factors, occlusal vertical dimension (OVD), and radiographic data . The preference of a removable design will be influenced by the need for lip and cheek support, which often can be predicted by the thickness of a buccal flange of an existing complete denture .…”
Section: Selection Of Fixed or Removable Implant Prosthetic Designmentioning
confidence: 99%
See 1 more Smart Citation